Exploring the cultivation of digital skills among Islamic Education Teachers in teaching and learning in Selangor Darul Ehsan - Mohd Zainudin, Nur ‘Atieqah; Huda, Miftachul (Journal of Islamic, Social, Economics and Development, 2025)
Digital skills among Islamic Education teachers play an important role in ensuring the effectiveness of teaching and learning in the modern technological era. This study aims to explore the acculturation of digital skills among Islamic Education teachers in Selangor through a qualitative approach involving face-to-face interviews with nine teachers, document analysis and classroom observations. The study findings reveal that the level of technology integration is still limited, with most teachers only at the Substitution and Augmentation levels in the SAMR model, without reaching a higher level of learning transformation. In response to this challenge, this study proposes the Islamic Education Teachers Digital Skills Integration Model (MIKD-GPI) which consists of three main components: Technology Training and Mastery, Infrastructure and Institutional Support, and Digital-Based Pedagogical Transformation. This model is based on the TPACK and SAMR frameworks, and aims to improve teachers' understanding of effectively incorporating technology into teaching and learning. In conclusion, this study contributes to the academic discussion on the acculturation of digital skills by offering a model that can help teachers move to a higher level of technology integration. The implications of this study emphasize the need for systematic professional training, improved technological infrastructure, and strong institutional support to ensure the success of digital skills in Islamic Education. Future studies are suggested to evaluate the effectiveness of this model in a broader educational context.